The relationship between miR-21, DNA methylation, and bisphenol a in bovine COCs and granulosa cells - Sabry, Reem; May, Diana R.; Favetta, Laura A. (Frontiers in Cell and Developmental Biology, 2023)
miR-21 is a critical microRNA for the regulation of various processes in oocytes and granulosa cells. It is involved in the modulation of apoptosis and can influence other epigenetic mechanisms. Among these mechanisms, DNA methylation holds significant importance, particularly during female gametogenesis. Evidence has demonstrated that microRNAs, including miR-21, can regulate DNA methylation. Bisphenol A (BPA) is a widespread chemical that disrupts oocyte maturation and granulosa cell function. Recent findings suggested that BPA can act through epigenetic pathways, including DNA methylation and microRNAs. This study explores the involvement of miR-21 in the regulation of DNA methylation in bovine Cumulus-Oocyte-Complexes (COCs) and granulosa cells, in the presence and absence of BPA. Our results reveal that BPA reduces 5mC levels in granulosa cells but not in COCs, which can be attributed to a decrease in the methylating enzymes DNMT1 and DNMT3A, and an increase in the demethylating enzyme TET2. We observed a significant increase in the protein levels of DNMT1, DNMT3A, and TET2 upon inhibition of miR-21 in both COCs and granulosa cells. These findings directly imply a strong correlation between miR-21 signaling and the regulation of DNA methylation in bovine COCs and granulosa cells under BPA exposure.